The Role of Jet Bubble Column Technology in Domestic Wastewater Treatment at Pesantren Zaadul Ma’ad - Yuniar; Didiek Hari Nugroho; Yuliansyah Yuliansyah (Warta LPM, 2026)
Domestic wastewater in Islamic boarding schools is commonly managed using simple holding ponds without standardized treatment, resulting in high turbidity, elevated suspended solids, ammonia accumulation, and low dissolved oxygen levels. These conditions negatively affect environmental quality, sanitation, and the health of the community. Pesantren Zaadul Ma’ad experienced similar problems, with initial wastewater characteristics showing low dissolved oxygen (3.85 mg/L), turbidity of 49.3 NTU, total suspended solids (TSS) of approximately 50 mg/L, and ammonia concentrations around 30 mg/L. This community engagement program aimed to apply Jet Bubble Column (JBC) technology to improve wastewater quality and to strengthen the capacity of students and teachers in managing simple wastewater treatment systems. The program was carried out using a structured Participatory Action Research (PAR) approach, consisting of socialization, operational training, installation of the JBC unit, operational mentoring, periodic monitoring, and sustainability planning. The JBC system was installed in the wastewater holding pond and integrated with a multilayer filtration unit. Water quality monitoring was conducted using portable instruments to measure pH, dissolved oxygen (DO), total dissolved solids (TDS), turbidity, total suspended solids (TSS), and ammonia (NH₃). The implementation of JBC technology resulted in significant improvements in wastewater quality. DO levels increased to above 5 mg/L, ammonia concentrations decreased by 80–90%, TSS levels were reduced by more than 50%, and turbidity dropped to below 1 NTU. These improvements indicate a transition from anaerobic to stable aerobic conditions, highlighting the effectiveness of microbubble aeration combined with multilayer filtration in treating domestic wastewater. Beyond the technical results, the program strengthened local management capacity through the training of internal operators, the development of standard operating procedures (SOPs), and the integration of sanitation topics into educational activities. Recommended follow-up actions include optimizing the JBC design for greater efficiency, expanding the use of treated water for non-consumptive purposes, and replicating the model in other boarding schools as part of a broader effort to support decentralized and sustainable wastewater management systems.